Trivalent chromium chemical conversion treatment liquid for zinc or zinc alloy base material and method for using same

By using a trivalent chromium chemical conversion treatment solution containing zirconium, nitrate and chain colloidal silica on the surface of zinc or zinc alloy, the use of 6valent chromium and cobalt compounds in the prior art was solved, and the effect of high corrosion resistance and silver-white finished product appearance was achieved.

CN119776815APending Publication Date: 2025-04-08DIPSOL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411912161.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-09-14
Filing Date
2018-09-12
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, the chromate chemical conversion coating used for metal surfaces of zinc or zinc alloys contains harmful hexavalent chromium, and the use of cobalt compounds has problems of unstable supply and environmental protection restrictions.

Method used

By adding zirconium ions, nitrate ions and chain colloidal silica to the trivalent chromium chemical conversion treatment solution, and adjusting the pH value of the treatment solution to the range of 2.5 to 5.0, a chemical conversion film with excellent corrosion resistance, silver-white and white mist-free without hexavalent chromium is formed.

Benefits of technology

A high corrosion resistance, silver-white and uniform finished product appearance is achieved on the surface of zinc or zinc alloys, while avoiding the use of 6-valent chromium and cobalt compounds, and environmentally friendly treatment solutions are considered.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776815A_ABST
    Figure CN119776815A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy base material, said trivalent chromium chemical conversion treatment liquid being capable of forming a highly corrosion-resistant chemical conversion coating that also takes into account the environment. The present invention provides a hexavalent chromium-free trivalent chromium chemical conversion treatment liquid for zinc or zinc alloys, which is characterized by containing trivalent chromium ions, zirconium ions, nitrate ions and chain colloidal silica, and by having a pH of 2.5-5.0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with Chinese application number 201811061194.0 (the invention name of the original application is "Trivalent chromium chemical conversion treatment liquid for zinc or zinc alloy substrate and method using the same", and the application date of the original application is September 12, 2018). Technical Field

[0002] The present invention relates to a novel chemical conversion treatment liquid for forming a silvery white and uniform chemical conversion film having a non-fogging (non-white fogging) finished appearance and excellent corrosion resistance on the surface of zinc or zinc alloy metal, and a chemical conversion treatment method using the same. Background Art

[0003] Chemical conversion treatment is a technology that has been used for a long time to impart corrosion resistance to metal surfaces, and is now also used for surface treatment of aircraft, building materials, automobile parts, etc. However, chemical conversion treatment films represented by chromate chemical conversion treatment contain some harmful hexavalent chromium.

[0004] Hexavalent chromium is a regulated object in the WEEE (Waste Electrical and Electronic Equipment) Directive, the RoHS (Restriction of Hazardous Substances) Directive, the ELV (End of Life Vehicles) Directive, etc., and research on chemical conversion treatment liquids using trivalent chromium instead of hexavalent chromium is being actively carried out and industrialized (Japanese Patent Publication No. 2003-166074). In addition, in particular, for trivalent chromium chemical conversion treatment liquids without hexavalent chromium, cobalt compounds are often used to improve corrosion resistance. Cobalt is one of the so-called rare metals, and due to the expansion of its use or the limited number of producing countries, it is not necessarily in a stable supply system.

[0005] In addition, cobalt chloride, cobalt sulfate, cobalt nitrate, and cobalt carbonate are also SVHC (Substances of Very High Concern) regulated by REACH (Registration, Evaluation, Authorization and Restriction of Chemicals), and there is a trend to restrict their use.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-166074

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 7-11454 Summary of the invention

[0010] In view of the above-mentioned current situation, the present invention aims to provide a trivalent chromium chemical conversion treatment solution for zinc or zinc alloy substrates that can form a highly corrosion-resistant chemical conversion film that also takes the environment into consideration. Furthermore, the present invention aims to provide a trivalent chromium chemical conversion treatment solution that can form a high corrosion resistance equivalent to zinc-nickel alloy plating and a good finished product appearance without white haze even for zinc plating.

[0011] The present inventors have conducted intensive studies to achieve these two problems, and as a result, have found that by adding zirconium ions, nitrate ions and chain colloidal silica to a trivalent chromium chemical conversion treatment liquid containing trivalent chromium ions but not hexavalent chromium, and by adjusting the pH of the chemical conversion treatment liquid to a specific pH range, a chemical conversion treatment liquid can be obtained that can form a chemical conversion film on the surface of zinc and zinc alloys that has excellent corrosion resistance, a uniform finished appearance that is silvery white and free of white mist, and is also environmentally friendly, thereby completing the present invention.

[0012] That is, the present invention provides a trivalent chromium chemical conversion treatment liquid for zinc or zinc alloy substrates free of hexavalent chromium, characterized in that it contains trivalent chromium ions, zirconium ions, nitrate ions and chain colloidal silica, and the pH of the treatment liquid is 2.5 to 5.0.

[0013] In addition, the present invention provides a chemical conversion treatment method, comprising bringing the above-mentioned chemical conversion treatment solution into contact with a zinc or zinc alloy substrate.

[0014] According to the present invention, a trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy substrate can be provided which can form a chemical conversion film having excellent corrosion resistance and a uniform finished appearance of silvery white without white haze and taking the environment into consideration even without containing hexavalent chromium or cobalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a diagram showing chain-like colloidal silica and spherical colloidal silica. DETAILED DESCRIPTION

[0016] The substrate used in the present invention is not particularly limited as long as the surface can be coated with zinc or a zinc alloy, and examples thereof include various metals such as iron, nickel, copper, and their alloys, or metals such as aluminum subjected to zinc substitution treatment, and the shapes of the alloys are various substrates such as plates, rectangular parallelepipeds, columns, cylinders, and spheres. Specifically, examples thereof include disc brake calipers, etc.

[0017] The substrate is plated with zinc or zinc alloy by conventional methods. In order to precipitate the zinc coating on the substrate, any of acidic and neutral baths such as sulfuric acid bath, fluorinated borate bath, potassium chloride bath, sodium chloride bath, ammonium chloride compromise bath, cyanide bath, zincate bath, pyrophosphate bath, and other alkaline baths may be used. An acidic bath is preferred. In addition, the zinc alloy coating may be any of alkaline baths such as ammonium chloride bath and organic chelate bath.

[0018] In addition, as the zinc alloy plating, zinc-iron alloy plating, zinc-nickel alloy plating, zinc-cobalt alloy plating, tin-zinc alloy plating, etc. can be cited. Preferably, it is a zinc-nickel alloy plating. The thickness of the zinc or zinc alloy plating precipitated on the substrate can be arbitrary, and can be 1 μm or more, preferably 5 to 25 μm thick.

[0019] In the present invention, after the zinc or zinc alloy plating layer is precipitated on the substrate, a pretreatment is appropriately performed as needed, such as water washing or nitric acid activation treatment after water washing, and then a chemical conversion treatment is performed using the trivalent chromium chemical conversion treatment solution for the zinc or zinc alloy substrate of the present invention by a method such as immersion treatment.

[0020] The trivalent chromium chemical conversion treatment liquid of the present invention does not substantially contain hexavalent chromium ions, but contains trivalent chromium ions, zirconium ions, nitrate ions and chain colloidal silica. The pH of the treatment liquid is 2.5 to 5.0.

[0021] The trivalent chromium compound that provides trivalent chromium ions is not particularly limited, but is preferably water-soluble. Examples of the trivalent chromium compound include trivalent chromium salts such as chromium chloride, chromium sulfate, chromium nitrate, chromium phosphate, and chromium acetate. Alternatively, hexavalent chromium ions such as chromic acid and dichromate may be reduced to trivalent chromium ions using a reducing agent. These trivalent chromium compounds may be used alone or in combination of two or more. The content of trivalent chromium ions in the treatment liquid is 2 to 200 mmol / L, preferably 5 to 100 mmol / L, and more preferably 10 to 80 mmol / L. By making the content of trivalent chromium ions within such a range, excellent corrosion resistance can be obtained. In addition, in the present invention, if trivalent chromium is used in such a low concentration range, it is also advantageous in terms of drainage treatment and economy.

[0022] The zirconium compound providing zirconium ions is not particularly limited, and is preferably water-soluble. As the zirconium compound, for example, inorganic zirconium compounds or their salts such as zirconium nitrate, zirconium oxynitrate, ammonium zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, sodium zirconium carbonate, lithium zirconium carbonate, fluorozirconic acid (H2ZrF6) and its salts (such as sodium salts, potassium salts, lithium salts and ammonium salts) and organic zirconium compounds such as zirconium acetate, zirconium lactate, zirconium tartrate, zirconium malate and zirconium citrate can be cited. As the zirconium compound, fluorozirconic acid (H2ZrF6) and its salts, such as sodium salts, potassium salts, lithium salts and ammonium salts of fluorozirconic acid (H2ZrF6) are preferred. (NH4)2ZrF6). These zirconium compounds can be used alone or in combination of two or more. The content of zirconium ions in the treatment solution is 1 to 300 mmol / L, preferably 2 to 150 mmol / L, and more preferably 5 to 50 mmol / L. By setting the content of zirconium ions to be within such a range, excellent corrosion resistance can be obtained.

[0023] In the present invention, the molar ratio of trivalent chromium ions to zirconium ions (trivalent chromium ions / zirconium ions) is preferably 0.1 to 4, more preferably 0.2 to 3.5, and even more preferably 0.3 to 3. By setting the molar ratio of trivalent chromium ions to zirconium ions to be within such a range, a chemical conversion film having excellent appearance and corrosion resistance can be obtained.

[0024] The nitrate compound providing nitrate ions is not particularly limited, but is preferably water-soluble. Examples of the nitrate compound include nitric acid, ammonium nitrate, sodium nitrate, potassium nitrate, lithium nitrate, and the like. These nitrate compounds may be used alone or in combination of two or more. The content of nitrate ions in the treatment solution is 30 to 400 mmol / L, preferably 40 to 300 mmol / L, and more preferably 50 to 200 mmol / L. By making the content of nitrate ions within such a range, excellent appearance and corrosion resistance can be obtained.

[0025] In the present invention, Figure 1As shown, chain colloidal silica is different from the commonly used spherical colloidal silica, and is composed of several to a dozen primary particles of colloidal silica connected in a chain. Chain colloidal silica can be straight chain or branched. The average particle size of the primary particles of colloidal silica is preferably 5 to 20 nm, more preferably 10 to 15 nm. Chain colloidal silica preferably has primary particles connected and linked to a length of 20 to 200 nm, more preferably 40 to 100 nm. The length of chain colloidal silica is the total length of the main chain and the length of the branch. The size of chain colloidal silica is 20 to 200 nm in length. These chain colloidal silica can be used alone or in combination of two or more. The concentration of chain silica is 25 to 600 mmol / L, preferably 30 to 450 mmol / L, more preferably 40 to 300 mmol / L. By setting the content of the chain colloidal silica to be within such a range, excellent appearance and corrosion resistance can be obtained. Such chain colloidal silica can be obtained as a commercial product. For example, ST-UP and ST-OUP manufactured by Nissan Chemical Co., Ltd. can be cited.

[0026] The trivalent chromium chemical conversion treatment solution for zinc or zinc alloy substrate of the present invention can form an excellent corrosion-resistant film on the surface of zinc or zinc alloy coating even if it does not contain cobalt ions. However, cobalt ions may be further contained. When cobalt ions are contained, the content is preferably 300mmol / L or less, more preferably 100mmol / L or less, and further preferably 50mmol / L or less. The cobalt compound providing the cobalt ions is not particularly limited, but is preferably water-soluble. As the cobalt compound, for example, cobalt nitrate, cobalt chloride, cobalt sulfate, etc. may be cited. These cobalt compounds may be used alone or in combination of two or more.

[0027] The trivalent chromium chemical conversion treatment liquid for zinc or zinc alloy substrates of the present invention may further contain fluoride ions. The content of fluoride ions is preferably 6 to 1800 mmol / L, more preferably 30 to 300 mmol / L. Fluoride ions serve as counter ions for zirconium ions, and by making the content of fluoride ions within such a range, zirconium ions can be stabilized.

[0028] The fluorine-containing compound providing fluorine ions is not particularly limited. As the fluorine-containing compound, for example, hydrofluoric acid, fluoroboric acid, ammonium fluoride, hexafluorozirconic acid or its salt, etc. can be cited, preferably hexafluorozirconic acid or its salt. These fluorine-containing compounds can be used alone or in combination of two or more.

[0029] The trivalent chromium chemical conversion treatment liquid for zinc or zinc alloy substrates of the present invention may further contain a water-soluble carboxylic acid or a salt thereof. The content of the water-soluble carboxylic acid or a salt thereof is preferably 0.1 g / L to 10 g / L, more preferably 0.5 g / L to 8 g / L, and further preferably 1 g / L to 5 g / L. By making the content of the water-soluble carboxylic acid or a salt thereof within such a range, the trivalent chromium ions can be stabilized by forming a complex with the trivalent chromium ions. The molar ratio of the trivalent chromium ions to the water-soluble carboxylic acid or a salt thereof is preferably 0.5 to 1.5.

[0030] The water-soluble carboxylic acid is not particularly limited, and examples thereof include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, and suberic acid, which can be represented by R1-(COOH)2〔R1=C0~C8〕, and preferably oxalic acid and malonic acid, wherein R1=C0 and C1, respectively. As salts of water-soluble carboxylic acids, examples thereof include salts of alkali metals such as potassium and sodium, salts of alkaline earth metals such as calcium and magnesium, and ammonium salts. These water-soluble carboxylic acids or their salts may be used alone or in combination of two or more.

[0031] The trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy substrate of the present invention may further contain a water-soluble metal salt containing a metal selected from the group consisting of Zn, Al, Ti, Mo, V, Ce and W.

[0032] Examples of water-soluble metal salts include K2TiF6, etc. These water-soluble metal salts can be used alone or in combination of two or more. The content of the water-soluble metal salt is preferably 0.1 g / L to 1.5 g / L, more preferably 0.2 g / L to 1.0 g / L.

[0033] The trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy substrate of the present invention may further contain a phosphorus compound.

[0034] Examples of the phosphorus compound include NaH2PO2 (sodium hypophosphite). These phosphorus compounds may be used alone or in combination of two or more. The content of the phosphorus compound is preferably 0.01 g / L to 1.0 g / L, more preferably 0.1 g / L to 0.5 g / L.

[0035] The pH of the trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy substrate of the present invention is in the range of 2.5 to 5.0, preferably in the range of 3.0 to 4.5, and more preferably in the range of 3.0 to 4.0.

[0036] To adjust the pH to this range, an inorganic acid or organic acid such as nitric acid or hydrochloric acid, an alkaline agent such as ammonia, ammonium salts, caustic soda, sodium carbonate, potassium carbonate, or ammonium carbonate can be used. By adjusting the pH to this range, excellent appearance and corrosion resistance can be obtained.

[0037] The remainder of the above-mentioned components in the trivalent chromium chemical conversion treatment liquid for a zinc or zinc alloy substrate of the present invention is water.

[0038] There is no particular limitation on the method of forming a trivalent chromium chemical conversion film on a zinc or zinc alloy coating using the trivalent chromium chemical conversion treatment solution for a zinc or zinc alloy substrate of the present invention, and a known method can be applied. The substrate coated with zinc or zinc alloy is brought into contact with the chemical conversion treatment solution by methods such as immersion. When immersing, the temperature of the chemical conversion treatment solution is preferably 20 to 60°C, more preferably 30 to 40°C. The immersion time is preferably 5 to 600 seconds, more preferably 30 to 300 seconds. In addition, in order to activate the surface of the zinc or zinc alloy coating, it can be immersed in a dilute nitric acid solution (5% nitric acid, etc.) or a dilute sulfuric acid solution, a dilute hydrochloric acid solution, a dilute hydrofluoric acid solution, etc. before the trivalent chromium chemical conversion treatment. Conditions and treatment operations other than those described above can be carried out according to the conventional hexavalent chromate treatment method.

[0039] The trivalent chromium chemical conversion film formed on the zinc or zinc alloy plated layer using the trivalent chromium chemical conversion treatment solution for zinc or zinc alloy substrates of the present invention contains trivalent chromium, zirconium and chain silicon dioxide, and does not contain hexavalent chromium.

[0040] Next, the present invention will be described using examples and comparative examples, but the present invention is not limited to these examples.

[0041] Example

[0042] In Examples 1 to 5 and Comparative Examples 1 to 4, as galvanized test pieces, test pieces in which 9 to 10 μm zincate zinc plating (NZ-98 manufactured by Dipsol) was applied on the surface of a 0.5×50×70 mm patterned steel plate (pear ground steel plate) were used. The galvanized test pieces were immersed in a 5% nitric acid aqueous solution at room temperature for 10 seconds, and then the surface was thoroughly rinsed with running tap water to clean the surface. Next, the galvanized test pieces were subjected to the following chemical conversion treatment. After the test pieces subjected to the chemical conversion treatment were thoroughly washed with tap water and ion exchange water, they were allowed to stand in an electric drying oven maintained at 80°C for 10 minutes to dry.

[0043] (Example 1)

[0044] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.7 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 35° C. for 60 seconds.

[0045] (A) 40% chromium nitrate 5.4 g / L (as Cr 3+ Ion is 9mmol / L, NO3 - Ion is 27mmol / L)

[0046] (B) Potassium fluorozirconate: 2.0 g / L (7 mmol / L in terms of Zr ions)

[0047] (C) Ammonium nitrate: 4.8 g / L (as NO3 - Ion is 60mmol / L)

[0048] (D) Chain colloidal silica (particle size 40-100nm): 20.0g / L (50mmol / L)

[0049] The remainder is water.

[0050] (Example 2)

[0051] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 45° C. for 40 seconds.

[0052] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0053] (B) 40% Fluorozirconic acid: 7.8 g / L (15 mmol / L in terms of Zr ions)

[0054] (C) Sodium nitrate: 7.2 g / L (as NO3 - Ion is 85mmol / L)

[0055] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0056] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0057] The remainder is water.

[0058] (Example 3)

[0059] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0060] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0061] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0062] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0063] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0064] The remainder is water.

[0065] (Example 4)

[0066] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 20 seconds.

[0067] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0068] (B) Potassium fluorozirconate: 2.8 g / L (10 mmol / L in terms of Zr ions)

[0069] (C) Ammonium nitrate: 8.0 g / L (as NO3 - Ion is 100mmol / L)

[0070] (D) Chain colloidal silica (particle size 40-100nm): 108.0g / L (270mmol / L)

[0071] The remainder is water.

[0072] (Example 5)

[0073] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0074] (A) 40% chromium nitrate: 11.9 g / L (as Cr 3+ Ion is 20mmol / L, NO3 - Ion is 60mmol / L)

[0075] (B) Ammonium hexafluorozirconate: 1.9 g / L (8 mmol / L in terms of Zr ions)

[0076] (C) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0077] (D) Sodium nitrate: 7.2 g / L (as NO3 - Ion is 85mmol / L)

[0078] (E) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0079] The remainder is water.

[0080] (Comparative Example 1)

[0081] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0082] (A) 40% chromium nitrate: 11.9 g / L (20 mmol / L as Cr, 20 mmol / L as NO3 - Ion is 60mmol / L)

[0083] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0084] (C) Sodium nitrate: 3.4 g / L (as NO3 - Ion is 40mmol / L)

[0085] (D) Spherical colloidal silica (particle size 10-15nm): 26.5g / L (100mmol / L)

[0086] The remainder is water.

[0087] (Comparative Example 2)

[0088] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 2.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0089] (A) 35% chromium chloride: 8.1 g / L (as Cr 3+ Ion is 18mmol / L)

[0090] (B) Ammonium hexafluorozirconate: 2.2 g / L (9 mmol / L in terms of Zr ions)

[0091] (C) Sodium nitrate: 7.2 g / L (as NO3 - Ion is 85mmol / L)

[0092] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0093] The remainder is water.

[0094] (Comparative Example 3)

[0095] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 2.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0096] (A) 40% chromium nitrate: 47.7 g / L (as Cr 3+ Ion is 80mmol / L, NO3 - Ion count is 240mmol / L)

[0097] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0098] (C) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0099] (D) Oxalic acid dihydrate: 3.8 g / L (30 mmol / L in terms of oxalic acid)

[0100] Malonic acid: 3.1 g / L (30 mmol / L based on malonic acid)

[0101] (E) Chain colloidal silica (particle size 40-100nm): 48.0g / L (120mmol / L)

[0102] The remainder is water.

[0103] (Comparative Example 4)

[0104] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0105] (A) 40% chromium sulfate: 9.8 g / L (as Cr 3+ Ion is 20mmol / L)

[0106] (B) Ammonium hexafluorozirconate: 2.2 g / L (9 mmol / L in terms of Zr ions)

[0107] (C) Cobalt chloride hexahydrate: 4.1 g / L (17 mmol / L in terms of Co ions)

[0108] (D) Oxalic acid dihydrate: 3.8 g / L (30 mmol / L in terms of oxalic acid)

[0109] Malonic acid: 3.1 g / L (30 mmol / L based on malonic acid)

[0110] (E) Spherical colloidal silica (particle size 70-100nm): 26.5g / L (100mmol / L)

[0111] The remainder is water.

[0112] In Examples 6 to 10 and Comparative Examples 5 and 6, as galvanized test pieces, test pieces in which a 9 to 13 μm acid bath zinc plating layer (EZ-985CS manufactured by Dipsol) was applied on the surface of a 0.5×50×70 mm patterned steel plate were used. The galvanized test pieces were immersed in a 5% nitric acid aqueous solution at room temperature for 10 seconds, and then the surface was thoroughly rinsed with running tap water to clean the surface. Next, the galvanized test pieces were subjected to the following chemical conversion treatment. After the test pieces subjected to the chemical conversion treatment were thoroughly washed with tap water and ion exchange water, they were allowed to stand in an electric drying oven maintained at 80°C for 10 minutes to dry.

[0113] (Example 6)

[0114] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 45° C. for 40 seconds.

[0115] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0116] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0117] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0118] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0119] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0120] The remainder is water.

[0121] (Example 7)

[0122] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0123] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0124] (B) Potassium fluorozirconate: 2.6 g / L (9 mmol / L in terms of Zr ions)

[0125] (C) Sodium nitrate: 7.2 g / L (as NO3 - Ion is 85mmol / L)

[0126] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0127] The remainder is water.

[0128] (Example 8)

[0129] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 20 seconds.

[0130] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0131] (B) 40% Fluorozirconic acid: 5.2 g / L (10 mmol / L in terms of Zr ions)

[0132] (C) Ammonium nitrate: 8.0 g / L (as NO3 - Ion is 100mmol / L)

[0133] (D) Chain colloidal silica (particle size 40-100nm): 107.9g / L (270mmol / L)

[0134] The remainder is water.

[0135] (Example 9)

[0136] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0137] (A) 40% chromium nitrate: 6.0 g / L (as Cr 3+ Ion is 10mmol / L, NO3 - Ion is 30mmol / L)

[0138] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr ions)

[0139] (C) Ammonium nitrate: 8.0 g / L (as NO3 - Ion is 100mmol / L)

[0140] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0141] The remainder is water.

[0142] (Example 10)

[0143] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0144] (A) 35% chromium chloride: 13.6 g / L (as Cr 3+ Ion is 30mmol / L)

[0145] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr ions)

[0146] (C) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0147] (D) Sodium nitrate: 2.6 g / L (as NO3 - Ion is 30mmol / L)

[0148] (E) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0149] The remainder is water.

[0150] (Comparative Example 5)

[0151] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 2.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0152] (A) 40% chromium nitrate: 23.9 g / L (as Cr 3+ Ion is 40mmol / L, NO3 - Ion is 120mmol / L)

[0153] (B) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0154] (C) Oxalic acid dihydrate: 1.9 g / L (15 mmol / L in terms of oxalic acid)

[0155] Malonic acid: 1.6 g / L (15 mmol / L as malonic acid)

[0156] (D) Spherical colloidal silica (particle size 10-15nm): 26.5g / L (100mmol / L)

[0157] The remainder is water.

[0158] (Comparative Example 6)

[0159] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0160] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0161] (B) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0162] (C) Malonic acid: 6.2 g / L (60 mmol / L as malonic acid)

[0163] (D) Sodium nitrate: 1.7 g / L (as NO3 - Ion is 20mmol / L)

[0164] (E) Spherical colloidal silica (particle size 70-100nm): 26.5g / L (100mmol / L)

[0165] The remainder is water.

[0166] In Examples 11 and 12 and Comparative Examples 7 and 8, as the zinc-nickel alloy plated test piece, a test piece in which a zincate zinc-nickel alloy plating layer (IZ-250 manufactured by Dipsol) of 9 to 10 μm was applied on the surface of a 0.5×50×70 mm patterned steel plate was used. The zinc-nickel alloy plated test piece was subjected to the following chemical conversion treatment. After the test piece subjected to the chemical conversion treatment was fully washed with tap water and ion exchange water, it was left to stand in an electric drying oven maintained at 80° C. for 10 minutes to dry it.

[0167] (Example 11)

[0168] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0169] (A) 40% chromium sulfate: 9.8 g / L (as Cr 3+ Ion is 20mmol / L)

[0170] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr ions)

[0171] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0172] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0173] (D) Chain colloidal silica (particle size 40-100nm): 20.0g / L (50mmol / L)

[0174] The remainder is water.

[0175] (Example 12)

[0176] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0177] (A) 40% chromium nitrate: 6.0 g / L (as Cr 3+ Ion is 10mmol / L, NO3 - Ion is 30mmol / L)

[0178] (B) 40% Fluorozirconic acid: 10.4 g / L (20 mmol / L in terms of Zr ions)

[0179] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0180] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0181] The remainder is water.

[0182] (Comparative Example 7)

[0183] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0184] (A) 40% chromium sulfate: 9.8 g / L (as Cr 3+ Ion is 20mmol / L)

[0185] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr)

[0186] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0187] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0188] (D) Spherical colloidal silica (particle size 10-15nm): 13.3g / L (50mmol / L)

[0189] The remainder is water.

[0190] (Comparative Example 8)

[0191] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 4.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 25° C. for 60 seconds.

[0192] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0193] (B) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0194] (C) Sodium nitrate: 3.4 g / L (as NO3 - Ion is 40mmol / L)

[0195] (D) Oxalic acid dihydrate: 2.5 g / L (20 mmol / L in terms of oxalic acid)

[0196] The remainder is water.

[0197] In Examples 13 to 17 and Comparative Examples 9 to 11, as galvanized test pieces, test pieces in which a 5 to 25 μm (depending on the location) acidic zinc bath coating (EZ-985CS manufactured by Dipsol) was applied to a disc brake caliper (raw material FCD-450) were used. The galvanized test piece was immersed in a 5% nitric acid aqueous solution at room temperature for 10 seconds, and then the surface was thoroughly rinsed with running tap water to clean the surface. Next, the galvanized test piece was subjected to the following chemical conversion treatment. After the test piece subjected to the chemical conversion treatment was thoroughly cleaned with tap water and ion exchange water, it was allowed to stand in an electric drying oven maintained at 80°C for 10 minutes to dry.

[0198] (Example 13)

[0199] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 45° C. for 40 seconds.

[0200] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0201] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0202] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0203] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0204] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0205] The remainder is water.

[0206] (Example 14)

[0207] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0208] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0209] (B) Potassium fluorozirconate: 2.6 g / L (9 mmol / L in terms of Zr ions)

[0210] (C) Sodium nitrate: 7.2 g / L (as NO3 - Ion is 85mmol / L)

[0211] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0212] The remainder is water.

[0213] (Example 15)

[0214] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 20 seconds.

[0215] (A) 40% chromium sulfate: 8.8 g / L (in Cr 3+ Ion is 18mmol / L)

[0216] (B) 40% Fluorozirconic acid: 5.2 g / L (10 mmol / L in terms of Zr ions)

[0217] (C) Ammonium nitrate: 8.0 g / L (as NO3 - Ion is 100mmol / L)

[0218] (D) Chain colloidal silica (particle size 40-100nm): 107.9g / L (270mmol / L)

[0219] The remainder is water.

[0220] (Example 16)

[0221] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0222] (A) 40% chromium nitrate: 11.9 g / L (as Cr 3+ Ion is 20mmol / L, NO3 - Ion is 60mmol / L)

[0223] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr ions)

[0224] (C) Ammonium nitrate: 8.0 g / L (as NO3 - Ion is 100mmol / L)

[0225] (D) Chain colloidal silica (particle size 40-100nm): 64.0g / L (160mmol / L)

[0226] The remainder is water.

[0227] (Example 17)

[0228] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0229] (A) 35% chromium chloride: 13.6 g / L (as Cr 3+ Ion is 30mmol / L)

[0230] (B) Ammonium hexafluorozirconate: 3.6 g / L (15 mmol / L in terms of Zr ions)

[0231] Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0232] (C) Sodium nitrate: 2.6 g / L (as NO3 - Ion is 30mmol / L)

[0233] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0234] The remainder is water.

[0235] (Comparative Example 9)

[0236] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0237] (A) 40% chromium nitrate: 11.9 g / L (as Cr 3+ Ion is 20mmol / L, NO3 - Ion is 60mmol / L)

[0238] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0239] (C) Sodium nitrate: 3.4 g / L (as NO3 - Ion is 40mmol / L)

[0240] (D) Spherical colloidal silica (particle size 10-15nm): 26.5g / L (100mmol / L)

[0241] The remainder is water.

[0242] (Comparative Example 10)

[0243] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 2.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 40° C. for 30 seconds.

[0244] (A) 40% chromium nitrate: 23.9 g / L (as Cr 3+ Ion is 40mmol / L, NO3 - Ion is 120mmol / L)

[0245] (B) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L in terms of Co ions, NO3 - Ion is 34mmol / L)

[0246] (C) Oxalic acid dihydrate: 1.9 g / L (15 mmol / L in terms of oxalic acid)

[0247] Malonic acid: 1.6 g / L (15 mmol / L as malonic acid)

[0248] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0249] The remainder is water.

[0250] (Comparative Example 11)

[0251] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.5 using caustic soda, the above-mentioned test piece was immersed in the liquid at 30° C. for 40 seconds.

[0252] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0253] (B) Ammonium hexafluorozirconate: 2.4 g / L (10 mmol / L in terms of Zr ions)

[0254] (C) Cobalt chloride hexahydrate: 4.1 g / L (17 mmol / L in terms of Co ions)

[0255] (D) Malonic acid: 6.2 g / L (60 mmol / L as malonic acid)

[0256] (E) Spherical colloidal silica (particle size 40-100nm): 26.5g / L (100mmol / L)

[0257] The remainder is water.

[0258] In Examples 18 and 19 and Comparative Examples 12 and 13, as zinc-nickel alloy plated test pieces, a disc brake caliper (raw material FCD-450) was plated with an acid zinc-nickel alloy layer (IZA-2500 manufactured by Dipsol) of 5 to 25 μm (depending on the location) was used. The zinc-nickel alloy plated test piece was subjected to the following chemical conversion treatment. After being fully washed with tap water and ion exchange water, the test piece subjected to the chemical conversion treatment was left to stand in an electric drying oven maintained at 80°C for 10 minutes to dry it.

[0259] (Example 18)

[0260] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0261] (A) 40% chromium sulfate: 4.9 g / L (as Cr 3+ Ion is 10mmol / L)

[0262] (B) Ammonium hexafluorozirconate: 1.7 g / L (7 mmol / L in terms of Zr ions)

[0263] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0264] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 -Ion is 5mmol / L)

[0265] (D) Chain colloidal silica (particle size 40-100nm): 20.0g / L (50mmol / L)

[0266] The remainder is water.

[0267] (Example 19)

[0268] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using aqueous ammonia, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0269] (A) 40% chromium nitrate: 3.0 g / L (as Cr 3+ Ion count is 5mmol / L, NO3 - Ion is 15mmol / L)

[0270] (B) 40% Fluorozirconic acid: 5.2 g / L (10 mmol / L in terms of Zr ions)

[0271] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0272] (D) Chain colloidal silica (particle size 40-100nm): 40.0g / L (100mmol / L)

[0273] The remainder is water.

[0274] (Comparative Example 12)

[0275] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 3.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 40° C. for 60 seconds.

[0276] (A) 40% chromium sulfate: 4.9 g / L (as Cr 3+ Ion is 10mmol / L)

[0277] (B) Ammonium hexafluorozirconate: 1.7 g / L (7 mmol / L in terms of Zr ions)

[0278] (C) Ammonium nitrate: 12.0 g / L (as NO3 - Ion is 150mmol / L)

[0279] Zinc nitrate hexahydrate: 0.75 g / L (as NO3 - Ion is 5mmol / L)

[0280] (D) Spherical colloidal silica (particle size 10-15nm): 13.3g / L (50mmol / L)

[0281] The remainder is water.

[0282] (Comparative Example 13)

[0283] A chemical conversion treatment liquid was prepared as follows, and after adjusting the pH to 4.0 using caustic soda, the above-mentioned test piece was immersed in the liquid at 25° C. for 60 seconds.

[0284] (A) 35% chromium chloride: 9.0 g / L (as Cr 3+ Ion is 20mmol / L)

[0285] (B) Cobalt nitrate hexahydrate: 5.0 g / L (17 mmol / L as Co ion, 17 mmol / L as NO3 - Ion is 34mmol / L)

[0286] (C) Sodium nitrate: 3.4 g / L (as NO3 - Ion is 40mmol / L)

[0287] (D) Oxalic acid dihydrate: 2.5 g / L (20 mmol / L in terms of oxalic acid)

[0288] The remainder is water.

[0289] The appearance of the chemical conversion film was evaluated from the viewpoints of color tone, uniformity, and gloss. The evaluation criteria for color tone are as follows.

[0290] (Good) Silvery white > Blue > Interference color > White (Poor)

[0291] In addition, the evaluation criteria for uniformity are as follows.

[0292] Good: Trivalent chromium chemical conversion coating has no white haze and is a uniform finished product

[0293] Bad: The trivalent chromium chemical conversion film has white fog and uneven finished product

[0294] The test pieces subjected to the chemical conversion treatment were subjected to a salt spray test (hereinafter referred to as SST) in accordance with JIS Z-2371, and the corrosion resistance was evaluated by the time for white rust generation and the time for red rust generation per 24 hours.

[0295] The results of Examples 1 to 5 are shown in Table 1, the results of Examples 6 to 10 are shown in Table 2, the results of Examples 11 and 12 are shown in Table 3, the results of Examples 13 to 17 are shown in Table 4, the results of Examples 18 and 19 are shown in Table 5, the results of Comparative Examples 1 to 4 are shown in Table 6, the results of Comparative Examples 5 and 6 are shown in Table 7, the results of Comparative Examples 7 and 8 are shown in Table 8, and the results of Comparative Examples 9 to 13 are shown in Table 9.

[0296] [Table 1] (Unit: mmol / L)

[0297]

[0298] [Table 2] (Unit: mmol / L)

[0299]

[0300] [Table 3] (Unit: mmol / L)

[0301]

[0302] [Table 4] (Unit: mmol / L)

[0303]

[0304] [Table 5] (Unit: mmol / L)

[0305]

[0306] [Table 6] (Unit: mmol / L)

[0307]

[0308] [Table 7] (Unit: mmol / )

[0309]

[0310] [Table 8] (Unit: mmol / L)

[0311]

[0312] [Table 9]

[0313]

Claims

1. A trivalent chromium chemical conversion treatment solution for zinc or zinc alloy without hexavalent chromium, characterized in that: Contains a trivalent chromium compound providing trivalent chromium ions, a zirconium compound providing zirconium ions, a nitrate compound providing nitrate ions, and chain colloidal silica. The cobalt compound that provides cobalt ions is not contained, or the cobalt compound that provides cobalt ions is contained so that the cobalt ion concentration in the treatment liquid is 300 mmol / L or less. The fluorine-containing compound that provides fluorine ions is not contained, or the fluorine-containing compound that provides fluorine ions is contained in a manner such that the fluorine ion concentration in the treatment liquid is 6 to 1800 mmol / L. The water-soluble carboxylic acid or its salt is not contained, or the water-soluble carboxylic acid or its salt is contained in a treatment liquid in such a manner that the concentration of the water-soluble carboxylic acid or its salt is 0.1 g / L to 10 g / L, The water-soluble metal salt is not contained, or the water-soluble metal salt containing the metal selected from Zn, Al, Ti, Mo, V, Ce and W is contained in the treatment solution in a concentration of 0.1 g / L to 1.5 g / L, The phosphorus compound is not contained, or the phosphorus compound is contained in the treatment liquid in such a manner that the phosphorus compound concentration is 0.01 g / L to 1.0 g / L, Does not contain inorganic acids, organic acids or alkaline agents for adjusting pH, or contains inorganic acids, organic acids or alkaline agents for adjusting pH, The rest is water, The pH of the treatment liquid is 3.0-3.7, the zinc alloy is zinc-iron alloy, zinc-nickel alloy or zinc-cobalt alloy, and the molar ratio of trivalent chromium ion to zirconium ion, that is, trivalent chromium ion / zirconium ion, is 0.1-4.

2. The chemical conversion treatment solution according to claim 1, wherein The concentration of trivalent chromium ions in the treatment liquid is in the range of 2 to 200 mmol / L.

3. The chemical conversion treatment liquid according to claim 2, wherein: The concentration of trivalent chromium ions in the treatment liquid is in the range of 5 to 100 mmol / L.

4. The chemical conversion treatment liquid according to claim 2, wherein: The concentration of trivalent chromium ions in the treatment liquid is in the range of 10 to 80 mmol / L.

5. The chemical conversion treatment liquid according to claim 1, wherein The concentration of zirconium ions in the treatment liquid is in the range of 1 to 300 mmol / L.

6. The chemical conversion treatment liquid according to claim 5, wherein: The concentration of zirconium ions in the treatment solution is in the range of 2 to 150 mmol / L.

7. The chemical conversion treatment liquid according to claim 5, wherein: The zirconium ion concentration in the treatment liquid is in the range of 5 to 50 mmol / L.

8. The chemical conversion treatment liquid according to claim 1, wherein The concentration of trivalent chromium ions in the treatment liquid is in the range of 2 to 200 mmol / L, and the concentration of zirconium ions is in the range of 1 to 300 mmol / L.

9. The chemical conversion treatment liquid according to claim 1, wherein: The average particle size of primary particles of the chain-like colloidal silica is 5 to 20 nm.

10. The chemical conversion treatment liquid according to claim 9, wherein: The average particle size of the primary particles of the chain-like colloidal silica is 10 to 15 nm.

11. The chemical conversion treatment liquid according to claim 1, wherein The length of the chain-like colloidal silica obtained by bonding the primary particles is 20 to 200 nm.

12. The chemical conversion treatment liquid according to claim 11, wherein: The length of the chain-like colloidal silica obtained by bonding the primary particles is 40 to 100 nm.

13. The chemical conversion treatment solution according to claim 1, wherein: The concentration of the chain colloidal silica in the treatment liquid is in the range of 25 to 600 mmol / L.

14. The chemical conversion treatment liquid according to claim 13, wherein: The concentration of the chain colloidal silica in the treatment liquid is in the range of 30 to 450 mmol / L.

15. The chemical conversion treatment liquid according to claim 13, wherein: The concentration of the chain colloidal silica in the treatment liquid is in the range of 40 to 300 mmol / L.

16. The chemical conversion treatment solution according to claim 1, wherein: The nitrate ion concentration in the treatment liquid is in the range of 30 to 400 mmol / L.

17. The chemical conversion treatment liquid according to claim 16, wherein: The nitrate ion concentration in the treatment liquid is in the range of 40 to 300 mmol / L.

18. The chemical conversion treatment liquid according to claim 16, wherein The nitrate ion concentration in the treatment liquid is in the range of 50 to 200 mmol / L.

19. The chemical conversion treatment solution according to claim 1, wherein The molar ratio of trivalent chromium ions to zirconium ions, that is, trivalent chromium ions / zirconium ions, is 0.2 to 3.

5.

20. The chemical conversion treatment solution according to claim 1, wherein: The molar ratio of trivalent chromium ions to zirconium ions, that is, trivalent chromium ions / zirconium ions, is 0.3 to 3.

21. The chemical conversion treatment solution according to claim 1, wherein The cobalt ion concentration in the treatment liquid is 100 mmol / L or less.

22. The chemical conversion treatment solution according to claim 1, wherein: The cobalt ion concentration in the treatment liquid is 50 mmol / L or less.

23. The chemical conversion treatment solution according to claim 1, wherein: The fluoride ion concentration in the treatment solution is 30 to 300 mmol / L.

24. The chemical conversion treatment solution according to claim 1, wherein: The concentration of the water-soluble carboxylic acid or its salt in the treatment liquid is 0.5 g / L to 8 g / L.

25. The chemical conversion treatment solution according to claim 1, wherein: The concentration of the water-soluble carboxylic acid or its salt in the treatment liquid is 1 g / L to 5 g / L.

26. The chemical conversion treatment solution according to claim 1, wherein: The concentration of the water-soluble metal salt in the treatment liquid is 0.2 g / L to 1.0 g / L.

27. The chemical conversion treatment solution according to claim 1, wherein: The concentration of the phosphorus compound in the treatment liquid is 0.1 g / L to 0.5 g / L.

28. The chemical conversion treatment solution according to claim 1, wherein: Furthermore, it contains cobalt ions at a concentration of 300 mmol / L or less, Contains fluoride ions at a concentration of 6 to 1800 mmol / L. Contains a water-soluble carboxylic acid or a salt thereof at a concentration of 0.1 g / L to 10 g / L, A water-soluble metal salt containing a metal selected from the group consisting of Zn, Al, Ti, Mo, V, Ce and W at a concentration of 0.1 g / L to 1.5 g / L, Contains phosphorus compounds at a concentration of 0.01 g / L to 1.0 g / L. The remainder is water.

29. A chemical conversion treatment method, comprising bringing the chemical conversion treatment liquid according to any one of claims 1 to 28 into contact with a surface of zinc or a zinc alloy, wherein the zinc alloy is a zinc-iron alloy, a zinc-nickel alloy or a zinc-cobalt alloy.

30. A chemical conversion treatment method, comprising immersing a surface of zinc or a zinc alloy in a chemical conversion treatment solution according to any one of claims 1 to 28, wherein the zinc alloy is a zinc-iron alloy, a zinc-nickel alloy or a zinc-cobalt alloy.

Citation Information

Patent Citations

  • Method for chromating metal by coating

    JP1995011454A

  • Treatment solution for forming hexavalent chromium- free rust preventive coating on plated film with zinc and zinc alloy, hexavalent chromium-free rust preventive coating and method for forming the same

    JP2003166074A